Preparing teachers to teach in complex settings: opportunities for professional learning and development - Flores, Maria Assunção (2020)
The preparation of prospective teachers to work in complex settings and the need to provide in-service teachers with relevant professional development opportunities are key themes in educational research, particularly in the European Journal of Teacher Education. These are more than ever two crucial topics as we face the current COVID-19 global pandemic. In times of a global lockdown, with the closure of schools and universities, the need to rapidly move from face-to-face teaching to online teaching entailed challenges for teachers, teacher educators and professional development providers as well as for policy makers. The COVID-19 pandemic has changed our everyday life in many ways and, in particular, the education sector. The implications and effects of the COVID-19 pandemic in education are yet to be known. However, the current situation makes evident and even exacerbates inequalities in access to education but it also entails opportunities to reshape education, teacher education and educational institutions. The ‘new normal’ has been announced and has already started in some contexts, but it also brings with it a number of challenges particularly as far as education and teacher education are concerned. Thus, a Special Issue in EJTE will be devoted to the COVID-19 pandemic and its implications for teacher education worldwide. It is expected that such Special Issue will be published in 2020.